2019
DOI: 10.37358/rc.19.10.7607
|View full text |Cite
|
Sign up to set email alerts
|

Thioctic Acid and Vitamin B Complex Improves Clinical Sings in Diabetic Peripheral Neuropathy

Abstract: Diabetic neuropathy is the most common cause of neuropathy worldwide and it is estimated to affect about half of people with diabetes. The goal of our study is to compare the effectiveness of thioctic acid treatment alone versus the efficacy of thioctic acid plus vitamin B complex in patients with diabetic peripheral polyneuropathy (DPN). We conducted a prospective, observational study staring from October 2017 to December 2018, in which we included 56 DPN patients. Depending on the Michigan neuropathic screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…However, no blinding was reported for this study. A small observational study reported improved outcomes in neuropathic symptoms for ALA and Milgamma combination therapy compared with ALA as a monotherapy 67 …”
Section: Commentmentioning
confidence: 99%
“…However, no blinding was reported for this study. A small observational study reported improved outcomes in neuropathic symptoms for ALA and Milgamma combination therapy compared with ALA as a monotherapy 67 …”
Section: Commentmentioning
confidence: 99%